A new process of combined pretreatment and dyeing: REST - YILMAZ, BURCU; ÖNER, ERHAN (ELSEVIER SCI LTD, 2011)
Use of enzymes in textile processes has many advantages as far as the environmentally friendly processes are concerned. These advantages include water and energy savings, less chemical use, less fabric damage, mild and environmentally friendly process conditions. In this work, C.I. Reactive Yellow 15, C.I. Reactive Red 21 and C.I. Reactive Blue 19 were used to dye untreated woven cotton fabric in a laboratory scale dyeing machine, on a pilot scale jig and on a pilot scale winch by using a single bath combined process, in which various enzymes, namely, amylase, pectinase, and catalase were employed. This new process was named as the Rapid Enzymatic Single-bath Treatment (REST), since it was completed almost in half of the conventional dyeing time, and all of the stages, namely, desizing, scouring, bleaching and dyeing were carried out in a single bath without replacing the process water with fresh water until the end of the dyeing. In the REST process, the untreated, starch-sized fabric was first desized by amylase enzyme, and this was followed by a pectinase treatment in the same bath. The fabric was then bleached by H2O2 in the same bath, and after the hydrogen peroxide bleaching; the catalase enzyme was added to the bath to remove H2O2 residues before reactive dyeing. Without carrying out intermediate washings/rinsings between these processes, the reactive dyeing was carried out in a conventional way in the same bath, and finally, the fabric was taken from the bath and washed out. The colour yield was compared with the dyeings which were carried out conventionally in separate baths. Finally, the REST has many benefits in terms of water saving, reduced process time and energy consumptions compared to the conventional preparatory and dyeing process of cotton fabrics. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Enzymes; Combined-dyeing; Environmentally friendly dyeing process; Reactive dyeing of cotton; COTTON